(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
Brands’ perspectives on consumption and consumers have strongly changed during the pandemic because, lately, they have focused on medical care and innovation. The context of advertising campaigns requires a different approach with specific communication characteristics: safety, medical care, protection, family assistance. The present study focuses on the advertising discourse delivered by retailers on the market to answer consumers’ needs. There are two types of perspectives to be considered here: encouraging consumption to survive and looking for solutions and psychological support to get over de-socialisation and fears. Retailers turn from simple suppliers into innovative volunteers who concern themselves with how to diminish fears and insecurity. As a research method, I conducted a multimodal discourse analysis focused on the online advertisements running on Facebook and Instagram to unfold communication strategies, linguistic tools, brand values, and techniques of adaptation to the pandemic. The period considered relevant for this study was during the Romanian lockdown, between March 16 and May 16, 2020, plus another month afterward to observe the consequences of brands’ attitudes towards consumers.